2019
DOI: 10.1038/s41746-019-0104-2
|View full text |Cite
|
Sign up to set email alerts
|

Automation of the kidney function prediction and classification through ultrasound-based kidney imaging using deep learning

Abstract: Prediction of kidney function and chronic kidney disease (CKD) through kidney ultrasound imaging has long been considered desirable in clinical practice because of its safety, convenience, and affordability. However, this highly desirable approach is beyond the capability of human vision. We developed a deep learning approach for automatically determining the estimated glomerular filtration rate (eGFR) and CKD status. We exploited the transfer learning technique, integrating the powerful ResNet model pretraine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(92 citation statements)
references
References 44 publications
(45 reference statements)
4
85
1
2
Order By: Relevance
“…What is more, Kuo et al identified the CKD status defined by an eGFR of <60 ml/min/1.73 m2 based on 4,505 kidney ultrasound images by deep neural network (The AUC of the model is 0.904). A Pearson correlation coefficient of 0.741 and accuracy of 85.6% indicated the strong relationship between AI and creatinine-based GFR estimations [48].…”
Section: Imaging Diagnosismentioning
confidence: 95%
“…What is more, Kuo et al identified the CKD status defined by an eGFR of <60 ml/min/1.73 m2 based on 4,505 kidney ultrasound images by deep neural network (The AUC of the model is 0.904). A Pearson correlation coefficient of 0.741 and accuracy of 85.6% indicated the strong relationship between AI and creatinine-based GFR estimations [48].…”
Section: Imaging Diagnosismentioning
confidence: 95%
“…Machine learning and rapidly developing deep learning-based technologies have exhibited their ability to convert these big data into a usable form in biomedical applications. In general, the implementation of AI and ML in the healthcare field have improved the welfare of the patients (Lundberg et al, 2018;Saria et al, 2010;Marella et al, 2017), improved quality of healthcare and effective diagnosis (Kuo et al, 2019;Rumsfeld et al, 2016;Liang et al, 2019), and also have lowered the healthcare costs (Bates et al, 2014;Özdemir and Barshan, 2014;Lo-Ciganic et al, 2015). Though a huge amount of data is available, most of them are never used for building mathematical models that can be integrated with health care system (Weintraub et al, 2018) and it is seen that only about 15% of the hospitals are currently using these technologies even then the usage accounts only for limited purposes (Zeng and Luo, 2017).…”
Section: Artificial Intelligence and Machine Learningmentioning
confidence: 99%
“…Kuo et al (14) developed a convolutional deep learning (AI) model for the prediction of glomerular filtrate and the stage of renal failure from ultrasound images of the kidneys. Even this effort, while providing encouraging results, needs further development in order to be implemented in the clinic.…”
Section: The Importance Of Telemedicine and Artificial Intelligencementioning
confidence: 99%